Communication and Teamwork During Telemedicine-Enabled Stroke Care in an Ambulance. (February 2022) - Joseph, Anjali; Chalil Madathil, Kapil; Jafarifiroozabadi, Roxana; Rogers, Hunter; Mihandoust, Sahar; Khasawneh, Amro; McNeese, Nathan; Holmstedt, Christine; McElligott, James T.
Objective: The purpose of this study is to understand the communication among care teams during telemedicine-enabled stroke consults in an ambulance. Background: Telemedicine can have a significant impact on acute stroke care by enabling timely intervention in an ambulance before a patient reaches the hospital. However, limited research has been conducted on understanding and supporting team communication during the care delivery process for telemedicine-enabled stroke care in an ambulance. Method: Video recordings of 13 simulated stroke telemedicine consults conducted in an ambulance were coded to document the tasks, communication events, and flow disruptions during the telemedicine-enabled stroke care delivery process. Results: The majority (82%) of all team interactions in telemedicine-enabled stroke care involved verbal interactions among team members. The neurologist, patient, and paramedic were almost equally involved in team interactions during stroke care, though the neurologist initiated 48% of all verbal interactions. Disruptions were observed in 8% of interactions, and communication-related issues contributed to 44%, with interruptions and environmental hazards being other reasons for disruptions in interactions during telemedicine-enabled stroke care. Conclusion: Successful telemedicine-enabled stroke care involves supporting both verbal and nonverbal communication among all team members using video and audio systems to provide effective coverage of the patient for the clinicians as well as vice versa. Application: This study provides a deeper understanding of team interactions during telemedicine-enabled stroke care that is essential for designing effective systems to support teamwork.